ANALISIS HUBUNGAN ANTARA FAKTOR SECURITY IN THE HANDLING OF PRIVATE DATA (SHPD) DAN TRUST DENGAN E-COMMERCE WEBSITELOYALTY (Studi Pada Zalora.co.id dan Bhinneka.com) - Irsyad Asmarandhi; Alila Pramiyanti (Center for Economic Studies Universitas Katolik Parahyangan, 2014)
Abstract The increasing of netizen number has been making internet be a convince media on product selling. Indonesia has been proved to be a nation with the fastest growth in Asia-Pacific for online transaction. Besides, the amount of transaction value increases rapidly in every year. The purpose of this paper is to analyze the close relationship between Security in the Handling of Private Data (SHPD) and Trust by E-Commerce Website Loyalty. Methodology or research approach is a quantitative descriptive with primary data accumulation by means of online questionnaire. Based on 50 valid responses for Zalora and same number for Bhinneka who had made purchase is collected from survey, the analysis technique of this research is descriptive. In addition to did correlation analysis by t-test in Partial Least Square Path Modelling (PLS-PM) technology was employed to examine the research model and close relationship between all variables. The study of three research hypotheses revealed that the correlation between SHPD and Trust was positive and significant by 73,29%. The correlation between Trust and Loyalty was positive and significant by 52,03%. The correlation between SHPD and Loyalty was significant by 45,85% however the line was opposite. Based on values, it found out the another factor out of models which had a correlation with. Those another factor estimated as satisfaction, consumer emotional commitment, awareness, payment system, enquickness, logistics service, etc.